Implementing Vocabulary Teaching Strategies for Students with Disabilities - Herianto; Abdullah; Geminastiti Sakkir (Universitas Islam Negeri Palopo, 2026)
This research examines the use of vocabulary teaching techniques by English teachers for students with disabilities within a special education framework. The research is based on inclusive education concepts, highlighting the significance of adaptive and student-centered teaching methods to support learners with different needs, including those with hearing impairments. Vocabulary acquisition is a crucial aspect of English language learning; yet, children with disabilities frequently encounter challenges stemming from restricted auditory availability, cognitive diversity, and communication obstacles. These issues necessitate that educators implement instructional methodologies that transcend traditional teaching methods. This study utilized a qualitative descriptive research approach to thoroughly investigate classroom-based teaching strategies. The study was performed at SLB Negeri Wonomulyo. Data were gathered by non-participant classroom observations, comprehensive interviews, and document analysis involving one English instructor and eighth-grade students with disabilities. Classroom observations were conducted over six educational sessions to identify consistent teaching patterns and instructional methods. The gathered data were examined utilizing an interactive model that encompassed data condensation, data presentation, and conclusion formulation. The results indicate that the educator employs many interrelated tactics for vocabulary instruction. This encompasses tailored training according to students' proficiency levels, multisensory methodologies utilizing visual aids, gestures, and Total Physical Response (TPR), collaboration with a teaching assistant, sequential instructional design, and methodical repetition. Vocabulary is presented incrementally, first with tangible visual representations, succeeded by Indonesian explanations, and ultimately English word forms to guarantee understanding prior to memory. Furthermore, classroom management is implemented using a humanistic approach bolstered by collaborative effort. The study emphasizes that effective vocabulary learning for children with disabilities necessitates adaptable, flexible, and collaborative pedagogical approaches. The findings provide empirical insights into inclusive vocabulary instruction within special education settings and have practical implications for English educators dealing with challenged students.